Natural convection of nanofluids in a cavity with linearly varying wall temperature - Sivanandam Sivasankaran (Maejo International Journal of Science and Technology, 2010)
The aim of the present numerical study is to investigate the convective flow and heat transfer behaviour of nanofluids with different nano-particles in a square cavity. The hot left wall temperature of the cavity is varied linearly with height whereas the cold right wall temperature is kept constant. The finite volume method is used to discretise the transport equations, which are solved by iterative method. Numerical simulations are carried out for different combinations of pertinent parameters involved in the study. It is found that the heat transfer rate increases on increasing the volume fraction of the nanofluid for all types of nanoparticles considered. The increment in average Nusselt number is strongly dependent on the nanoparticle chosen.